The concept and principles of sustainable architectural design for national parks in Serbia - Milošević Predrag (Spatium, 2004)
The paper elaborates the concept of sustainable architectural design that has come to the forefront in the last 20 years, and in the light of the National Park. This concept recognizes that human civilization is an integral part of the natural world and that nature must be preserved and perpetuated if the human community itself is to survive. Sustainable design articulates this idea through developments that exemplify the principles of conservation and encourage the application of those principles in our daily lives. A corollary concept, and one that supports sustainable design, is that of bio-regionalism - the idea that all life is established and maintained on a functional community basis and that all of these distinctive communities (bio-regions) have mutually supporting life systems that are generally self-sustaining. The concept of sustainable design holds that future technologies must function primarily within bioregional patterns and scales. They must maintain biological diversity and environmental integrity contribute to the health of air, water, and soils, incorporate design and construction that reflect bio-regional conditions, and reduce the impacts of human use. Sustainable design, sustainable development, design with nature environmentally sensitive design, holistic resource management - regardless of what it's called, "sustainability," the capability of natural and cultural systems being continued over time, is the key. Sustainable design must use an alternative approach to traditional design and the new design approach must recognize the impacts of every design choice on the natural and cultural resources of the local, regional, and global environments. Sustainable park and recreation development will succeed to the degree that it anticipates and manages human experiences. Interpretation provides the best single tool for shaping experiences and sharing values. By providing an awareness of the environment, values are taught that are necessary for the protection of the environment. Sustainable design will seek to affect not only immediate behaviors but also the long-term beliefs and attitudes of the visitors.